Indirect and Induced Benefit-Cost Analysis: A Case Study - Haring, Joseph E.; Deventer, Allen Van (The Review of Economics and Statistics, 1978)
Carnoy, Martin, Class Analysis and Investment in Human Resources: Dynamic Model, Review of Radical Political Economics 3 (1971), 56-81. Corcoran, Mary, Christopher Jencks, and Michael Olneck, Effects of Family Background on Earnings, The American Review 66 (May 1976), 430-435. Duncan, Otis Dudley, A Socio-Economic Index for all Occupations, in Albert J. Reiss, Otis Dudley Duncan, P. K. Hatt, and C. C. North (eds.), Occupation and Social Status (New York: Free Press of Glencoe, 1961). Fishlow, Albert, and Human Capital: Some Further Results for Brazil, mimeograph, 1974. Griliches, Zvi, and William M. Mason, Education, Income and Ability, Journal of Political Economy 80 (May/June 1972), S74-S103. Kasnakoglu, Zehra, Distribution in Turkey: Study on the Determinants of Male Earnings Differentials in 1968, Ph.D. thesis, University of Wisconsin, Madison, 1975. , A Study on the Determinants of Male Income Differentials in Turkey for 1968, Hacettepe Bulletin of Natural Sciences and Engineering 5 (June 1976), 90-122. Mincer, Jacob, Schooling, Experience and Earnings (New York: Columbia University Press, 1974). Morgenstern, Richard D., Direct and Indirect Effects on Earnings of Schooling and Socio-economic Background, this REVIEW 55 (May 1973), 225-233. Ribich, Thomas L., and James L. Murphy, Economic Returns to Increased Educational Spending, Journal of Human Resources 10 (Winter 1975), 56-77.